2012
DOI: 10.1017/s0950268812001306
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus genotypes in children in the Basque Country (North of Spain): rapid and intense emergence of the G12[P8] genotype

Abstract: SUMMARYBetween July 2009 and June 2011, rotavirus was detected in 507 of 4597 episodes of acute gastroenteritis in children aged <3 years in Gipuzkoa (Basque Country, Spain), of which the G-type was determined in 458 (90·3%). During the annual seasonal epidemic of 2010–2011, the unusual G-type 12 was predominant, causing 65% (145/223) of cases of rotavirus gastroenteritis. All the G12 strains were clustered in lineage III and were preferentially associated with P-type 8. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
2
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 28 publications
5
24
2
7
Order By: Relevance
“…Other characteristics of the rotavirus cases during the second year of the study suggested that G12P[8]-associated diarrhea might be clinically slightly less severe than diarrhea caused by other strains. Only 1 previous study compared characteristics of a G12 epidemic with characteristics of previous epidemics in which G1 or G9 strains were dominant, and no difference in mean age and hospitalization rates was found ( 15 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other characteristics of the rotavirus cases during the second year of the study suggested that G12P[8]-associated diarrhea might be clinically slightly less severe than diarrhea caused by other strains. Only 1 previous study compared characteristics of a G12 epidemic with characteristics of previous epidemics in which G1 or G9 strains were dominant, and no difference in mean age and hospitalization rates was found ( 15 ). …”
Section: Discussionmentioning
confidence: 99%
“…Since 2000, the prevalence of G1 strains has been declining, and other genotypes, such as G9 and G12, have emerged ( 9 ). In Africa, G12 strains were first detected in southern Africa, mostly in association with P[6] ( 10 12 ), and G12P[8] recently emerged as a predominant strain in western Africa ( 13 , 14 ) and some regions of Spain ( 15 ), Argentina ( 16 ), and the United States ( 17 ). …”
mentioning
confidence: 99%
“…G12 RVA are considered emerging human RVA strains, and the lineage III G12 allele has spread worldwide rapidly [18, 19]. Strain G12P[8] was associated with a large outbreak of pediatric gastroenteritis in Rochester in 2007 (an outbreak detected through the NSVN) [13], and this genotype has been reported recently in Niger [20], Spain [21], Nicaragua [22], Haiti [23], and Australia [24]. It appears that G12P[8] strains now are established in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, there are at least five common G types (G1-G4 and G9), and three common P types (P[4], P[6] and P[8]) circulating worldwide (Banyai et al, 2012; Gentsch et al, 2005; Patel et al, 2011; Santos and Hoshino, 2005) Other previously uncommon G and P types (e.g., G5, G8, G12, P[14], P[19]) have been more frequently associated with human disease in the last decade (Chitambar et al, 2011; Cilla et al, 2012; Cunliffe et al, 2001; Esona et al, 2009a; Esona et al, 2009b; Matthijnssens et al, 2009a; Saikruang et al, 2013). These reports highlighted reassortment based interspecies and zoonotic transmission of RVAs (Gentsch et al, 2005; Martella et al, 2010).…”
mentioning
confidence: 99%